Pengembangan Desa Wisata Berbasis Pemberdayaan Masyarakat di Desa Karang Tengah, Kabupaten Bogor: Pendekatan Terpadu Untuk Optimalisasi Potensi Lokal - Mujio Mujio; Vely Brian Rosandi; Novida Waskitaningsih; Keisya Rania Zahirah; Irma Yunita Chaniago (Institut Pertanian Bogor, 2026)
Karang Tengah Village, Babakan Madang Subdistrict, Bogor Regency, has the potential for nature-based tourism that is developed through community participation. However, the management of village tourism is not yet supported by integrated governance and strong institutions, so coordination between tourism stakeholders is still informal. This community service activity aims to assist village officials and the Sentul Local Guide Association in designing a more integrated and sustainable tourism village development plan. The approach used in this community service activity is participatory, involving stakeholder mapping, identification and prioritisation of issues, formulation of programme guidelines, and institutional strengthening. The results of the discussion showed that institutional issues were the main problem in village tourism development. Based on an analysis of the root causes, program guidelines were formulated, including strengthening the role of BUMDes, increasing the capacity of tourism managers, and developing a more coordinated village tourism system. The outputs of the activity were a stakeholder role-sharing matrix, a village tourism development work plan, and an integrated coordination model that placed local associations as the operational hub of tourism management. This activity increased the collective awareness and commitment of tourism actors in building more collaborative governance. This assistance was the first step in strengthening the institutional foundation as a prerequisite for the sustainability of community-based tourism villages.